2016
DOI: 10.1080/1357650x.2015.1134564
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between line bisection performance and emotion processing: Where do you draw the line?

Abstract: A recent study demonstrated that higher accuracy on a line bisection task related to greater ratings of evocative impact from paintings. The authors suggested that line bisection accuracy may act as a "barometer" for both visuospatial and emotion processing, likely as a function of overlapping neural correlates in the right temporoparietal region. We suggest and test an alternative explanation: that visuospatial bias interacted with asymmetries in the paintings and the rating scales to produce the apparent rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…They found that the evocative impact of the painting correlated with the line bisection bias (i.e., stronger emotional evocation-regardless of valence-was related to smaller rightward bias). However, Hatin and Tottenham [37] reported different findings when using the same paintings as Drago et al, presented in a mirrored and non-mirrored version. Using visual-analog and numeric scales, either ascending and descending, subjects rated the evocative impact of each painting and its mirror version, after which they performed a paper-and-pencil line bisection task.…”
Section: Artworkmentioning
confidence: 86%
See 1 more Smart Citation
“…They found that the evocative impact of the painting correlated with the line bisection bias (i.e., stronger emotional evocation-regardless of valence-was related to smaller rightward bias). However, Hatin and Tottenham [37] reported different findings when using the same paintings as Drago et al, presented in a mirrored and non-mirrored version. Using visual-analog and numeric scales, either ascending and descending, subjects rated the evocative impact of each painting and its mirror version, after which they performed a paper-and-pencil line bisection task.…”
Section: Artworkmentioning
confidence: 86%
“…Three studies examined how aesthetic judgments of paintings with emotional connotations affect pseudoneglect [36][37][38]. Drago et al [36] asked subjects to rate the evocative impact of each painting and to perform a paper-and-pencil line bisection task after painting viewing.…”
Section: Artworkmentioning
confidence: 99%
“…In some cases, spirals express negative emotions, and twirls show confusion and dizziness [ 18 ]. The visuospatial bias correlates with human emotion [ 19 ]. Thus, designers like to clearly express characters’ emotion by placing lines appropriately in the scenes of an animation [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whether being presented with a painting also affects the allocation of spatial attention as measured by line bisection, due to possible different recruitment of the two hemispheres during art-viewing, has never been directly investigated. This issue is even more interesting when considering that there may be a relationship between the "default" spatial attentional bias of an individual and her/his evocative reactions to visual art (i.e., the larger the leftward bias, the higher the emotional reaction of that individual to visual art; Drago et al, 2008), possibly due to spatial attention and emotional processing both involving the right temporo-parietal region (Drago et al, 2008; but see Hatin & Tottenham, 2016).…”
Section: Introductionmentioning
confidence: 99%